RISK FACTORS ASSESSMENT AND MOLECULAR CHARACTERIZATION OF THEILERIA IN SMALL RUMINANTS OF BALOCHISTAN - Mir A Khan; M. A. Khan; I. Ahmad3; M. S. Khan; A. A. Anjum; A. Z. Durrani; K. Hameed; I. U. Kakar; A.Wajid; M. Ramazan; Rafiuddin (Journal of Animal and Plant Sciences, 2017)
In Pakistan, theileriosis is an important disease of small ruminants due to favourable climatic conditions for ticks. The northern highlands of Balochistan were never been previously explored for theileriosis, so the present one year study (June 2012-May 2013) was designed to determine epidemiology and molecular characterization of Theileria in domestic small ruminants in two regions (Northern Highlands and Suleiman Mountain) of Balochistan, Pakistan. The domestic small ruminant flocks (n= 2200 sheep; n=670 goats) were visited for data collection and blood sampling. The samples were examined microscopically for the presence of Theileria in RBCs. The association of various risk factors with the disease were tested through Chi square test. The Prevalence of Theileriosis was higher in sheep than goats (20.81% vs 9.70%; p<0.05). We did not find any significant difference in the prevalence of disease in Northern Highlands and Suleiman Mountain Region of Balochistan (p>0.05). A clear trend of seasonal pattern (p<0.05) came to record with highest in summer season (30.30%) followed by autumn (19.07%), spring (14.52%) and winter (7.61%). The disease was significantly higher (p<0.05) in above two years age group (22.17%) followed by between 1-2years (15.85%) and lowest in less than one year (7.99%).  Gender was not a significant risk factors for theileriosis (18.92% male vs 17.92% female; p>0.05). The molecular characterization of positive samples through 18S ribosomal RNA revealed the presence of Theileria lestoquardi and Theileria ovis in the infected animals. T. lestoquardi was dominated in both sheep (73.80%) and goats (69.23%) while T. Ovis accounted for only 26.19% of sheep infection and 30.76% in goats.The observed prevalence can be explained by the farming system of the rural livestock of Balochistan, lack of awareness of community, absence of diagnostic facilities, expensive acaricidal drugs and poor economic condition of farmers.
Keywords: Theileriosis; T. lestoquardi; T. ovis; Balochistan; Small ruminants